2019
DOI: 10.3892/or.2019.7053
|View full text |Cite
|
Sign up to set email alerts
|

PD‑L1 promotes head and neck squamous cell carcinoma cell growth through mTOR signaling

Abstract: Programmed death-ligand 1 (PD-L1), an immune co-stimulatory molecule, is expressed on various cancer cells and the surface of immune cells. Its overexpression on tumor cells suppresses the immune response to promote tumor cell immune escape. The present study demonstrated that PD-L1 was critical in head and neck squamous cell carcinoma (HNSCC) carcinogenesis. Immunohistochemical analysis of HNSCC tissue microarrays revealed that PD-L1 was overexpressed in tumor tissue, and its expression increased as tumor mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…In breast cancer, PD-L1 could predict the outcome of patients (41). PD-L1 promoted tumor cell growth through mTOR signaling in head and neck squamous cell carcinoma carcinogenesis cell lines Cal-27 and Fadu (42). Consistent with these findings, the present study revealed that PD-L1 expression was decreased in patients with AML with complete remission compared with that in patients with relapsed or refractory in the 90 samples from patients with AML.…”
Section: Discussionsupporting
confidence: 87%
“…In breast cancer, PD-L1 could predict the outcome of patients (41). PD-L1 promoted tumor cell growth through mTOR signaling in head and neck squamous cell carcinoma carcinogenesis cell lines Cal-27 and Fadu (42). Consistent with these findings, the present study revealed that PD-L1 expression was decreased in patients with AML with complete remission compared with that in patients with relapsed or refractory in the 90 samples from patients with AML.…”
Section: Discussionsupporting
confidence: 87%
“…PD‐1 is also considered a marker for exhausted T cells and is often upregulated in CD4 + and CD8 + TILs in various types of cancers 30,31 . CD8 + TILs of human HNSCCs were found to express increased levels of PD‐1 on their surface, 32 and 66% to 79% of patients with SCC had PD‐L1‐positive tumor cells 33–36 . In addition, we previously showed that CD8 + TILs in a mouse SCC model highly expressed PD‐1 and LAG‐3 37 .…”
Section: T Cellsmentioning
confidence: 95%
“…Interestingly, the present findings also suggest that targeting PDL1 in MUC1-positive tumor-bearing mice inhibited tumor growth and elicited a stronger antitumor effect than that in MUC1-negative tumor-bearing mice. This provides further in vivo evidence of the tumor suppressor function of PDL1 ( 44 46 ).…”
Section: Discussionmentioning
confidence: 65%